Estimation of Direct Genetic Effects on Milk Yield and Lactation Length in the Aownoi Dairy Cooperative - Endris, Mohammed; Tumwasorn, Sornthep; Wongwan, Chaiwat; Sopannarath, Panwadee; Prasanpanich, Somkiert (Agriculture and Natural Resources, 2012)
This study aimed to estimate the direct genetic effects on actual milk yield and lactation length of Holstein crossbred dairy cows in the Aownoi Dairy Cooperative. The data comprised 869 lactation records from 850 cows that had calved during 2009–2010. The data were analyzed by the Restricted Maximum Likelihood Method and applying the Average Information Algorithm (AIREML) using univariate analysis. The factors having a direct effect on actual milk yield and lactation length were the year-season of calving (YS), the breed group of the cows and the lactation number. The investigated traits were lactation length and actual milk yield. The results showed that the overall mean (± SE) for milk yield and lactation length was 4,484.84 ± 13.60 kg.cow-1.lactation-1 and 376.94 ± 0.34 d, respectively. The lactation number had a signiﬁ cant effect on the actual milk yield but there was no signiﬁ cant effect of breed group, lactation number and year-season of calving on the lactation length. Estimates of heritability for the actual milk yield and lactation length were 0.22 ± 0.08 and 0.26 ± 0.09, respectively.